The Impact of Early Childhood Education on Early Achievement Gaps : Evidence from the Indonesia Early Childhood Education and Development Project - Jung, Haeil; Hasan, Amer (World Bank, Washington, DC, 2014)
This paper assesses whether the Indonesia Early Childhood Education and Development project had an impact on early achievement gaps as measured by an array of child development outcomes and enrollment. The analysis is based on longitudinal data collected in 2009 and 2010 on approximately 3,000 four-year-old children residing in 310 villages located in nine districts across Indonesia. The study begins by documenting the intent-to-treat impact of the project. It then compares the achievement gaps between richer and poorer children living in project villages with those of richer and poorer children living in non-project villages. There is clear evidence that in project villages, the achievement gap between richer and poorer children decreased on many dimensions. By contrast, in non-project villages, this gap either increased or stayed constant. Given Indonesia's interest in increasing access to early childhood services for all children, and the need to ensure more efficient spending on education, the paper discusses how three existing policies and programs could be leveraged to ensure that Indonesia's vision for holistic, integrated early childhood services becomes a reality. The lessons from Indonesia's experience apply more broadly to countries seeking to reduce early achievement gaps and expand access to pre-primary education.